Microhabitat Characteristics of Lapland Longspur, Calcarius lapponicus, Nests at Cape Churchill, Manitoba - Boal, Clint W; Andersen, David E (2005)
We examined microsite characteristics at 21 Lapland Longspur (Ca/carius /apponicus) nests and land cover types in which they occUlTed in Wapusk National Parle. Cape Churchill, Manitoba. Nests were located in four of six physiographic-vegetation land-cover types. Regardless of land-cover type. all but one nest was built on a pressure ridge or mound. Nests were built midway between the bottom and top of ridges or mounds with steeper slopes than was randomly available. Longspur nests had a distinctive southwest orientation (P < 0.(01). Longspurs selected nest sites that consisted of comparatively greater amounts of shrub species and lesser amounts of moss than were randomly available. Nests were generally well concealed by vegetation(mean =67.0%) and concealment was negatively associated with amount of graminoid species at the nest (P =0.0005). Our nesting habitat data may facilitate a better understanding of breeding Lapland Longspur habitat requirements, and